Corporate Entrepreneurship Activities through Strategic Alliances: A Resource‐Based Approach toward Competitive Advantage* - Teng, Bing‐Sheng (Journal of Management Studies, 2007)
abstract Corporate entrepreneurship (CE) activities may significantly benefit from interfirm strategic alliances, although such benefits have not been sufficiently examined in the literature. In this paper, a resource‐based framework is presented to examine how strategic alliances offer entrepreneurial firms needed resources that may not otherwise be available. We argue that CE activities are likely to lead to resource gaps. We compare various options to fill resource gaps, and identify the pros and cons of the alliance approach. We then discuss the resource conditions that provide competitive advantage for a firm, if alliances are properly used to help implement CE. Finally, we examine how different types of alliance (e.g. joint ventures, R&D alliances, and learning alliances) facilitate various CE activities, including innovation, corporate venturing, and strategic renewal.